Study the Effect of Polyethylene on Physical Properties of Asphaltic Cement - M.A. Al-ani, Taher (Iraqi Journal of Civil Engineering, 2005)
Abstract :- For improving the properties of asphaltic cement several materials such as sulfur, rubber, carbon black, polymers….etc. are used for this purposes. In this study low density Polyethylene (LDPE) used at different percentage (0%, 1%, 3%, 5% and 7%) by weight of the asphaltic cement and then the changes in the properties are evaluated by pentration test (ASTM D-5), softening point test (ASTM D-2398), and Kinematics viscosity test (ASTM D-2170). Temperature susceptibility was evaluated by using Penetration vescosity number ( P.V.N ). In addition to that stiffness modulus of asphalt cement was predectied by using van der pole’s nomograph. The study showed that the LDPE increase the hardening of asphalt cement at different percentage except at (1%), and decrease the susceptibility of asphaltic cement to temperature.